1915
DOI: 10.5962/bhl.title.34297
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the 1908 outbreak of foot-and-mouth disease in the United States

Abstract: The disease prevails in European countries and occasions great economic losses. The mortality is quite Ioav, the serious losses depending chiefly upon the diminution of the milk secretion and the loss of flesh in the affected animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

1954
1954
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…In the 1933 outbreak inoculation of these same species provided consistent "takes" only in swine with mild reaction in 4 of 9 horses. These findings were confirmed by Reppin and Pyl (1935) and Mohler (1933a) and they further indicated that the norse was easier to infect than previously suspected. 3rawford (1937) isolated 4 strains of the virus,"A, 'B, C, andODmand found that while all 4 were infectious for swine, only types" B"and"D"were infectious for the horse.…”
Section: Experimental Host Rangesupporting
confidence: 75%
“…In the 1933 outbreak inoculation of these same species provided consistent "takes" only in swine with mild reaction in 4 of 9 horses. These findings were confirmed by Reppin and Pyl (1935) and Mohler (1933a) and they further indicated that the norse was easier to infect than previously suspected. 3rawford (1937) isolated 4 strains of the virus,"A, 'B, C, andODmand found that while all 4 were infectious for swine, only types" B"and"D"were infectious for the horse.…”
Section: Experimental Host Rangesupporting
confidence: 75%
“…The source of contemporary brucellosis outbreaks in livestock within the GYE has been the subject of a contentious debate, particularly in recent years as the number of livestock cases has increased substantially across the tri-state region 22 . B. abortus was likely introduced into the GYE with infected cattle before 1917, when it was first detected in Yellowstone National Park (NP) 23 24 . Today, brucellosis continues to persist in wild bison ( Bison bison ) and elk ( Cervus canadensis ) populations, with occasional transmission to domestic bison and cattle.…”
mentioning
confidence: 99%
“…Before any systematic attempt is made to control porcine tuberculosis it will be necessary to determine the relative importance of the The potential danger of infected cow's milk is well known and has been clearly demonstrated by experiments such as that quoted by Mohler and Washburn (1938), in which a line of pigs was fed tuberculous milk for three days and later 83.3 per cent. were shown to be infected.…”
Section: Sources Of Infectionmentioning
confidence: 99%